A longitudinal evaluation of the Communication, Education and Public Awareness (CEPA) campaign for the Philippine crocodile Crocodylus mindorensis in northern Luzon, Philippines. Issue 1 (5th February 2016) - Cureg, M. C.; Bagunu, A. M.; van Weerd, M.; Balbas, M. G.; Soler, D.; van der Ploeg, J.
Abstract : The Philippine crocodile Crocodylus mindorensis is Critically Endangered and its range is restricted to a few localities in human‐dominated landscapes. Therefore, the survival of this species in the wild depends strongly on the support of local people. Communication and education are prerequisites for successful in situ conservation. Over a 12 year period, the Mabuwaya Foundation distributed posters, calendars and comic books, organized theatre shows, gave school lectures, facilitated community meetings and established a crocodile rearing station/visitor centre to mobilize local support for the conservation of the Philippine crocodile in the northern Sierra Madre in Luzon. This paper documents changes in people's awareness of and attitudes towards the conservation of the Philippine crocodile, and changes in people's behaviour in ten barangays (villages) in the municipality of San Mariano. Most people living in crocodile habitat now know that the Philippine crocodile is protected by law and support the conservation of the species in the wild. Hunting, the destruction of nests and the use of destructive fishing methods have all significantly declined in these areas. As a result of the integrated conservation programme, the Philippine crocodile population is slowly recovering.